KEMAMPUAN ISOLAT BAKTERI PENGHASIL INDOLE ACETIC ACID (IAA) DARI TANAH GAMBUT SAMPIT KALIMANTAN TENGAH - Sofyan Fauzi Larosa; Endang Kusdiyantini; Budi Raharjo; Antonius Sarjiya (Departemen Biologi, Fakultas Sains dan Matematika Undip, 2013)
Peat soil is present in many areas of Indonesia, one of them is in Sampit regency Central Kalimantan. Peat soil is a type of soil which has an extreme characteristic of pH around 3-5. However, it is presumed that there is bacteria that can produce growth hormones, such as IAA. This study aimed to determine the ability of bacterial isolated from peat garden and burned area in Sampit regency which could produce IAA. Several tests were carried out including bacterial isolation, purification isolates, growth at different pH conditions, as well as IAA production with the addition of L-Tryptophan precursors with different concentrations. The growth and concentration of IAA was measured using spectrophotometry with wavelength 600 nm to 530 nm for growth and IAA, respectively. Results showed that five isolates produced IAA, three isolates from peat garden area and two isolates from burned areas. All isolates showed the highest growth at pH 6, and the highest IAA production at 43.311 ppm was produced by TGK6 isolate with the addition of 300 ppm L-Tryptophan. Keywords: Indole Acetic Acid, Peat Soil, L-Tryptophan